2021
DOI: 10.5858/arpa.2021-0061-oa
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Corynebacterium kroppenstedtii in Granulomatous Lobular Mastitis Using Real-Time Polymerase Chain Reaction and Sanger Sequencing on Formalin-Fixed, Paraffin-Embedded Tissues

Abstract: Context.— Associations between granulomatous lobular mastitis (GLM) and Corynebacterium kroppenstedtii have been reported since 2002, but large scale studies to assess the actual prevalence of this bacterium in GLM have not been performed. Objective.— To assess the prevalence of C kroppenstedtii in GLM using real-time polymerase chain reaction and Sanger sequencing. Design.— … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…We found 16 English articles, [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and 4 Japanese ones (Table 1). [31][32][33][34] Corynebacterium (C.) kroppenstedtii was detected most frequently, followed by C. tuberculostearicum.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We found 16 English articles, [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and 4 Japanese ones (Table 1). [31][32][33][34] Corynebacterium (C.) kroppenstedtii was detected most frequently, followed by C. tuberculostearicum.…”
Section: Resultsmentioning
confidence: 99%
“…19 Therefore, recent articles indicated not only bacterial culture but also real-time polymerase chain reaction (PCR) and formalin-fixed, paraffin-embedded (FFPE) biopsy specimens analysis for detecting pathogenically Corynebacterium spp. 18,25 It is reported that real-time PCR of C. kroppenstedtii from FFPE sections was useful (39-69% positive) in IGM cases. 18,25 The histopathological feature is granulomatous inflammation with dense exudation of lymphocytes, plasma cells, epithelioid histiocytes, multinucleated giant cells and neutrophils.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 The most common isolates are C. kroppenstedtii, followed by C. amycolatum, and C. tuberculostearicum. [35][36][37] The bacillary microorganisms can be identified in the empty spaces by the high-power examination of the lesion, though negative cases are common due to the scarcity of bacteria and poor Gram staining. (38) According to Paviour et al, Corynebacterium could be proposed as a pathogenetic factor in IGM.…”
Section: Cystic Neutrophilic Granulomatous Mastitis (Cngm)mentioning
confidence: 99%
“…We recently reported our study assessing the prevalence of Corynebacterium kroppenstedtii in FFPE tissues by real-time PCR in a large cohort of GLM cases, the largest study of this type to date. 15 In this study, we included FFPE tissues from 67 cases fulfilling the histologic criteria of GLM as well as 10 cases of non-granulomatous breast abscess as controls. DNA was extracted from FFPE tissues of all 67 GLM cases as well as the 10 control cases and amplified SYBR real-time PCR with primers specifically targeting the Corynebacterium kroppenstedtii 16S rRNA gene region.…”
mentioning
confidence: 99%